Addressing the challenge of women's health in Africa : report of the Commission on Women's Health in the African region (WHO Regional Office for Africa BrazzavilleCG, 2012)
Seeks to shed light on the interrelationships between issues that have often been neglected in the drawing up and implementation of public health policy aimed at improving women's health. Draws attention to the many ways in which policy makers, with appropriately targeted and sustained investment, can have a profound impact on the health, well-being and empowerment of women in the African region.
Keywords: WOMEN'S HEALTH